Maternal behavioral and psychosocial factors associated with preterm birth: A systematic review - I Gusti Ngurah Wirya Hadinata; I Wayan Artana Putra (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Preterm birth (PTB), defined as delivery before 37 weeks of gestation, remains a major global health problem contributing to neonatal morbidity and mortality. Behavioral and psychosocial factors are increasingly recognized as important contributors to PTB incidence. Purpose: To identify and synthesize evidence regarding behavioral and psychosocial risk factors associated with preterm birth. Method: This study used a systematic review design based on PRISMA guidelines. Literature searches were conducted through PubMed, ScienceDirect, and Google Scholar using keywords related to preterm birth, behavioral factors, and psychosocial factors. Selected studies were analyzed qualitatively according to inclusion and exclusion criteria. Results: Five studies met the eligibility criteria. Maternal stress and low health control beliefs were associated with an increased likelihood of preterm birth in some studies. Evidence regarding smoking, alcohol consumption, diet, physical activity, depression, and psychological distress was limited or inconsistent across the included studies. Conclusion: Behavioral and psychosocial factors contribute to PTB risk. Comprehensive prenatal care should integrate psychosocial screening and behavioral assessment to improve maternal and neonatal outcomes.